2021
DOI: 10.1182/bloodadvances.2021004665
|View full text |Cite
|
Sign up to set email alerts
|

Impact of R-CHOP dose intensity on survival outcomes in diffuse large B-cell lymphoma: a systematic review

Abstract: The dilemma of whether to treat elderly patients with diffuse large B-cell lymphoma (DLBCL) with a full or reduced dose intensity (DI) of R-CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisolone+rituximab) is often faced by clinicians. We conducted a systematic review assessing the impact of R-CHOP DI on DLBCL survival outcomes, according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Protocols (PRISMA-P) guidelines. We searched MEDLINE, EMBASE, and Cochrane CENTRAL for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Maintaining (R)CHOP dose intensity is a priority as it is associated with better clinical outcomes. 12 In addition, better control of systemic disease might reduce the risk of CNS involvement. 43,44 In patients with known CNS involvement, maintaining the dose intensity of both HDMTX and (R)CHOP is crucial, as HDMTX is an integral component of the treatment plan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining (R)CHOP dose intensity is a priority as it is associated with better clinical outcomes. 12 In addition, better control of systemic disease might reduce the risk of CNS involvement. 43,44 In patients with known CNS involvement, maintaining the dose intensity of both HDMTX and (R)CHOP is crucial, as HDMTX is an integral component of the treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…This can be a particular concern as R-CHOP dose intensity is an independent predictor of outcomes in DLBCL, whereas the overall risk of CNS relapse is relatively low in comparison. 3,12 Whether used for treating known CNS involvement or as prophylaxis, it is imperative that HDMTX be administered in a manner that minimizes toxicity and preserves treatment dose intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Although reduction in chemotherapeutic dose was reported to be a risk factor for impaired treatment effect, 15,16 the risk may be minimized in very elderly patients 14 . A systematic review also showed that survival was not affected by reduced dose intensity of R‐CHOP in patients aged ≥80 years 17 . Because dose reduction in very elderly patients has already been attempted in real‐world clinical settings, the present study may not suggest a new practice.…”
Section: Characteristics Patients Aged ≥80 Years N = 1819mentioning
confidence: 71%
“…14 A systematic review also showed that survival was not affected by reduced dose intensity of R-CHOP in patients aged ≥80 years. 17 Because dose reduction in very elderly patients has already been attempted in real-world clinical settings, the present study may not suggest a new practice. However, the findings may have importance in providing new evidence for current practice.…”
Section: Risk Of Febrile Neutropenia In Very Elderly Patients Aged ≥8...mentioning
confidence: 89%
“…The addition of rituximab to CHOP remains controversial and some studies have reported improved outcomes while most did not observe any benefit. [13][14][15]…”
Section: Discussionmentioning
confidence: 99%